Why and how there should be more Europe in asylum policies - Melissa Berger; Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
The experiences of the ongoing refugee crisis in Europe highlight the failures of the current model of having the EU and its members states share responsibility for asylum policies. Based on standard criteria of fiscal federalism, this paper analyses the shortcomings of the status quo. We show that European asylum policies stand in sharp contradiction to the optimal assignment of tasks within a federal system. For example, the current system creates substantial incentives for free-riding and foregoes the potential benefits of European economies of scale. Given this diagnosis, we explore the pros and cons of different options for a more European approach. In particular, we analyze and provide estimates of the quantitative implications for the options of: (A) quotas that would distribute refugees across countries according to a pre-determined calculation of reception capacity; (B) EU financing of national service provision; and (C) EU service provision in asylum policies.
Keywords: 330